Mass Cytometry Analysis Reveals the Landscape and Dynamics of CD32a+ CD4+ T Cells From Early HIV Infection to Effective cART - Coindre, Sixtine; Tchitchek, Nicolas; Alaoui, Lamine; Vaslin, Bruno; Bourgeois, Christine; Goujard, Cecile; Avettand-Fenoel, Veronique; Lecuroux, Camille; Bruhns, Pierre; Le Grand, Roger; Beignon, Anne-Sophie; Lambotte, Olivier; et al. (Frontiers in Immunology, 2018)
CD32a has been proposed as a specific marker of latently HIV-infected CD4+ T cells. However, CD32a was recently found to be expressed on CD4+ T cells of healthy donors, leading to controversy on the relevance of this marker in HIV persistence. Here, we used mass cytometry to characterize the landscape and variation in the abundance of CD32a+ CD4+ T cells during HIV infection. To this end, we analyzed CD32a+ CD4+ T cells in primary HIV infection before and after effective combination antiretroviral therapy (cART) and in healthy donors. We found that CD32a+ CD4+ T cells include heterogeneous subsets that are differentially affected by HIV infection. Our analysis revealed that Naive (N), central memory (CM), and effector/memory (Eff/Mem) CD32a+ CD4+ T-cell clusters that co-express LILRA2 and CD64 activating receptors were more abundant in primary HIV infection and cART stages. Conversely, LILRA2- CD32a+ CD4+ T-cell clusters of either the TN, TCM, or TEff/Mem phenotype were more abundant in healthy individuals. Finally, an activated CD32a+ CD4+ TEff/Mem cell cluster co-expressing LILRA2, CD57, and NKG2C was more abundant in all HIV stages, particularly during primary HIV infection. Overall, our data show that multiple abundance modifications of CD32a+ CD4+ T-cell subsets occur in the early phase of HIV infection, and some of which are conserved after effective cART. Our study brings a better comprehension of the relationship between CD32a expression and CD4+ T cells during HIV infection.